EDUKASI TENTANG HIGIENE SANITASI KANDANG AYAM TENTANG PENCEGAHAN PENYAKIT DERMATITIS KONTAK PADA PEKERJA KANDANG AYAM DI DESA BULAN BULAN KABUPATEN BATU BARA - Ginting, Evfy Septriani (INSTITUT KESEHATAN DELI HUSADA, 2024)
Chicken coop hygiene and sanitation refer to efforts aimed at maintaining the cleanliness and health of the coop environment to prevent the spread of diseases, including contact dermatitis among workers. Contact dermatitis occurs due to direct exposure to irritants or allergens in unclean coop environments, such as dust, dirt, or chemicals. By keeping the coop clean, ensuring good ventilation, regularly cleaning equipment, and enforcing strict hygiene protocols like the use of personal protective equipment (PPE), the risk of infection and skin irritation among workers can be significantly reduced. The goal of this service program is to educate about Chicken Coop Hygiene and Sanitation for the Prevention of Contact Dermatitis in Chicken Coop Workers in Desa Bulan Bulan, Batu Bara Regency. Inadequate coop conditions, such as not being cleaned daily and lack of appropriate personal protective equipment (PPE), have also been shown to increase the incidence of dermatitis among workers. The accumulation of chicken waste in the coop encourages the spread of bacteria and insects, contributing to the high occurrence of dermatitis. This program highlights the importance of personal hygiene and proper coop sanitation in preventing dermatitis among poultry farm workers. Workers need education and training on the significance of personal hygiene and cleanliness within the coop, as well as regular sanitation procedures, to create a safer and healthier working environment.